Study of consumer acceptance on nugget made of catfish (Clarias gariepinus), snail (Pila ampullacea), and the combination - Ilza, Mirna; ', Junardi; ', Syahrul (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The aim of the research was to observe the consumer acceptance on the nugget made of catfish, snail and the combination of them. The raw material used as the main ingredients were that used were catfish, snail and combination of them at 5 level, 100% catfish (A1), 100% snail (A2), combination of 75 % catfish, and 25% snail (A3), 50% catfish and 50% snail (A4), and combintion of 25% catfish and 75 % snail (A5). The result showed that the highest consumer acceptance was produced by the treatment of A1 and A3. The best nugget produced was performed by the highest value of appearance, aroma, taste and texture. Based on the proximate composition, combination of 75% catfish and 25% snail (A3) produced nugget that contained 54,56% mouisture, 24,21% protein, 7,44% fat, and 4,48% ash.Keyword : : catfish, snail, nugget, consumer acceptance